Modeling Consumer and Industry Reaction to Renewable Support Schemes: Empirical Evidence from the USA and Applications for Russia - Balashova, Svetlana; Ratner, Svetlana; Gomonov, Konstantin; Berezin, Andrey (International Journal of Energy Economics and Policy, 2020)
In this work, we simulate the impact of some government support measures on the development of small-scale power generation based on photovoltaics (PV). Models constructed based on the data on the development of PV in three states of the USA, - Alaska, Pennsylvania and Washington - the climatic and infrastructural conditions in which are close to the conditions of the Russian regions included in a single energy system. Analyzing the share of electricity payments in the structure of income/expenses of the population of Russia and the United States, we prove that the constructed models are applicable to Russian conditions, but only after the enactment of the law on micro-generation and the adoption of relevant amendments to the tax code. Keywords: Renewable Energy Sources Support Programs, Microgeneration, Photovoltaics-Installations, Econometric Modeling JEL Classifications: O33, Q42, Q47, Q48 DOI: https://doi.org/10.32479/ijeep.8961